Kedudukan Desa Adat Dalam Mekanisme Pemerintahan Desa Menurut Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - I Wayan Wisadnya (Jurnal Ilmiah Raad Kertha, 2018)
Country of Indonesia is a multicultural country with variouscharacteristics or its regional identity. The cirri or identity is the existence of theLaw of the Republic of Indonesia 1945.Sebagai one example of the area that is stillvery strong to maintain the implementation of the existence of customs and cultureis the area of Bali.Melalui traditional village which is also called as PekramanVillage (Perda Bali Province on change on behalf of Provincial Law No. 3 of 2001on the village pekraman, Provincial Regulation Bali No. 3 Year 2003). Then sinceIndnesia independence has been established several laws that exclusively orindependently regulate about the village. The Law includes Law No. 22 of 1948 on the Law on Regional Government, Law No. 1 of 1957 on the Principles of RegionalGovernment, Law No. 19/1965 on Village Management, Law No. 5 Year 1974 onthe subject matter of governance in the region, Law no. 5 of 1979 on villageadministration, Law no 22 of 1999 on regional government, Law no 32 year 2004and lastly about law no 6 year 2014 on regional government concerning the village.Formally applied on January 15, 2016 after its implementing regulations. Thenbased on the background can be formulated its problem is how the implementationof Law no 6 year 2014 about the village ?. This study uses the normative methodthrough applicable legislation.